Individual-patient meta-analysis of three randomized trials comparing endovascular versus open repair for ruptured abdominal aortic aneurysm. Issue 10 (24th June 2015) - Sweeting, M J; Balm, R; Desgranges, P; Ulug, P; Powell, J T; ,
Abstract: Background: The benefits of endovascular repair of ruptured abdominal aortic aneurysm remain controversial, without any strong evidence about advantages in specific subgroups. Methods: An individual-patient data meta-analysis of three recent randomized trials of endovascular versus open repair of abdominal aortic aneurysm was conducted according to a prespecified analysis plan, reporting on results to 90 days after the index event. Results: The trials included a total of 836 patients. The mortality rate across the three trials was 31·3 per cent for patients randomized to endovascular repair/strategy and 34·0 per cent for those randomized to open repair at 30 days (pooled odds ratio 0·88, 95 per cent c.i. 0·66 to 1·18), and 34·3 and 38·0 per cent respectively at 90 days (pooled odds ratio 0·85, 0·64 to 1·13). There was no evidence of significant heterogeneity in the odds ratios between trials. Mean(s.d.) aneurysm diameter was 8·2(1·9) cm and the overall in-hospital mortality rate was 34·8 per cent. There was no significant effect modification with age or Hardman index, but there was indication of an early benefit from an endovascular strategy for women. Discharge from the primary hospital was faster after endovascular repair (hazard ratio 1·24, 95 per cent c.i. 1·04 to 1·47). For open repair, 30-day mortality diminished with increasing aneurysm neck length (adjusted odds ratio 0·69 (95 per cent c.i. 0·53 to 0·89) per 15 mm), but aortic diameter was not associated with mortality for either type of repair. Conclusion: Survival to 90 days following an endovascular or open repair strategy is similar for all patients and for the restricted population anatomically suitable for endovascular repair. Women may benefit more from an endovascular strategy than men and patients are, on average, discharged sooner after endovascular repair. Abstract : Strong evidence of equivalence